2020
DOI: 10.1080/23802359.2020.1829124
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of turnip (Brassica rapa. ssp. rapa): genome structure and phylogenetic analysis

Abstract: Complete chloroplast genome sequence of turnip (Brassica rapa. ssp. rapa): genome structure and phylogenetic analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…( 2020 ), Han et al. ( 2020 ), and mitochondrial genome studies by Xue et al. ( 2020 ), which suggest that B. juncea was maternally derived from B. rapa , thus confirming zicaitai as a variety of B. rapa .…”
Section: Discussionmentioning
confidence: 89%
“…( 2020 ), Han et al. ( 2020 ), and mitochondrial genome studies by Xue et al. ( 2020 ), which suggest that B. juncea was maternally derived from B. rapa , thus confirming zicaitai as a variety of B. rapa .…”
Section: Discussionmentioning
confidence: 89%
“…rapa (NC_049891) (Han et al. 2020 ), Cardamine abchasica (NC_060863) (Ru et al. 2020 ) , Cardamine amara (NC_036962) (Dann et al.…”
Section: Resultsmentioning
confidence: 99%
“…At the genomic level, the results of the phylogenetic relationship of the chloroplast and mitochondrial genome of turnip showed that turnip is closely related to B . rapa [ 52 , 53 ]. Results of homologous sequence alignment in this study may provide a new insight into the root development of B .…”
Section: Resultsmentioning
confidence: 99%